Cell viability and morphological effect of heterotrigona itama sp. (stingless bee) honey on malignant brain tumour cell line - Seerangan, Priatharsine (2016)
Introduction: Glioblastoma Multiforme (GBM), a type of primary brain tumor is found to account for almost 80% of these tumors and, therefore, signifying the frequent occurrence. In Malaysia, a constantly increasing incidence along with limitations on currently available therapy options had urged the need for newer approaches to be implemented. For centuries, honey, a sweet natural product has been described in traditional medicine for its various medicinal uses. However, until recently honeys have been both researched scientifically and exploited medicinally on its various kinds of photochemical constituents. Objectives: The study is aimed to evaluate the anticancer activity of honey sample produced by a stingless bee species (Heterotrigona itama sp) for morphological analysis and cytotoxic activity against malignant brain tumor cells to provide evidence on its anticancer effect. Methods: Human primary glioblastoma cell line; U87 and dBTRG, are grown exponentially and treated with honey concentrations of 2-10% for three sequential days (24h, 48h, 72h). Honey sample from the stingless bee Heterotrigona Itama sp. were collected under sterile condition. The cytotoxicity of honey is quantified using colorimetric MTS assay with treatment of 2-10% of stingless bee honey. The plates were incubated and absorbance value was measured using ELISA reader at 490nm. For morphological analysis, the cell lines were seeded into six-well plates, and treated with 2% to 10% concentration ofthe honey for 24, 48 and 72 hours. At the indicated time points, morphological changes were examined and recorded under light microscope. Apoptosis was determined at similar intervals and concentrations after staining the cells with a nucleic acid stain known as Acridine Orane/Propidum Iodide. Results: Overall, crude honey sample have higher cytotoxic activities on U87 than dBTRG cell lines in a dose dependent manner, with U87 cell line showing higher sensitivity towards the honey extract. For morphological analysis, honey treated cells exhibited morphological alteration such as nuclear shrinkage, chromatin condensation and fragmented nucleus indicating apoptotic cellular changes. Conclusion: In conclusion, Heterotrigona Itama sp. contains an in vitro cytotoxic activity against human glioma cell lines, therefore suggesting the anticancer effect of the stingless bee honey. Further study is however required which includes isolation and characterization of the anticancer agents.